GENETIC ANALYSIS IN GREEN GRAM (VIGNA RADIATA (L.) WILCZEK) SUBJECTED TO NORTH CAROLINA MATING DESIGN-I - P. S. BAINADE,; M. R. MANJARE,; S. G. DESHMUKH,; S. D. KUMBHAR, (The Bioscan, 2014)
Genetic studies were conducted on progenies developed in F2 generation of an intervarietal cross made between powdery mildew resistant parent BPMR 156 and powdery mildew susceptible parent SML-668 of green gram using NCD-1. Significant differences among females in males in sets for all the traits in the study were observed. Dominant variance were more pronounced except for the traits like plant height, pod cluster per plants, pods per plant, 100 seed weight and yield per plant indicating the importance of dominant gene effects for those traits. Partial dominance was observed for plant height, number of pods per plant and yield per plant.